The influence of socio-demographic factors in adopting good aquaculture practices: Case of aquaculture farmers in Malaysia - Samah, Rozana; Kamaruddin, Roslina (Canadian Center of Science and Education, 2015)
This study examined the influence of socio demographic characteristics on the level of Good Aquaculture Practices (GAqP) among aquaculture farmer in the Northern part of Peninsular Malaysia.Primary data was obtained from survey that was conducted on 121 brackishwater and freshwater pond aquaculture farmer in the states of Kedah and Penang.Descriptive analysis was applied to identify the socio-demographic characteristics of aquaculture farmer and their level of GAqP.Multiple Linear Regression model was used to analyze the relationship between socio-demographic factors and the level of GAqP.The findings has revealed that the level of GAqP among brackishwater pond farmer is satisfactory where almost 84 per cent of farmer practicing GAqP at the level of 60 per cent and above with the mean value of 71.9 per cent.While the mean level of GAqP for freshwater pond farmer was at 50.3 per cent with only 18.6 percent of them practicing GAqP at the level of 60 per cent and above.Age and having technical knowledge related to aquaculture were the main factors that significantly influence to the level of GAqP among aquaculture farmer. Therefore measures related to the enhancement of technical knowledge among aquaculture farmer should be deliberated in the formulation of aquaculture development programs to ensure the sustainable development of aquaculture in Malaysia.